Survival of critically ill patients with COVID-19 pneumonia-a single-center experience - Marina Stojanović; Biljana Miličić; Nemanja Purić; Jelena Jeremić; Marko Jović; Milan Stojčić; Maja Omčikus; Nikola Trboljevac; Jelena Velickovic (Journal of Infection in Developing Countries)
Introduction: The aim of the study was to determine the survival probability of critically ill patients with COVID-19 infection who needed mechanical ventilation and to determine the efficacy of Tocilizumab use.